Analyzing the Condition of Gear Module Using Internet of Things. Issue 1 (May 2021) - Venkatesh, T; Jamuna, R; Bharath, G; Arunprasath, M; Nishaji, A
Abstract: This project is focused on the use of the Internet of Things Vibration Detection. The assessment of passing motions in a system is vibration control. When unusual vibrations are detected, this project involves developing an SMS alert. It requires a laboratory-based vibration detection experiment when applying the different magnitude of the force. This force causes the sensor's values to change from their initial values. Acceleration values can be seen on the webpage and, if necessary, analysis can be done. The warning signal will be produced considering the maximum magnitude at which destruction is high. Using GSM technology, this message will be sent to various mobile phones. Properly performed, vibration monitoring can be extremely useful in identifying the extent of the damage and assessing the origin in order to avoid damage to structures. We are currently using our key parts, the Arduino microcontroller, the accelerometer sensor, and the GSM module. The Arduino Uno microcontroller's code is written in C++.